Preparation method and application of protein coupled water-phase CuInS quantum dots

The protein-coupled CuInS/ZnS quantum dots were synthesized through a one-pot two-step method, which solved the problems of immaturity and insufficient stability of ternary quantum dot synthesis technology, and achieved highly bioactive and low-cost quantum dot materials suitable for antibacterial and biological imaging.

CN120795905APending Publication Date: 2025-10-17ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510735830.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

The existing ternary I-III-VI quantum dots have immature synthesis technology and insufficient stability, which limits their application in complex biological systems. In addition, the biological application potential of traditional II-VI quantum dots is limited due to their biological toxicity.

Method used

Protein-coupled CuInS/ZnS quantum dots were synthesized using a one-pot two-step method. By adding protein modifiers lysozyme or bovine serum albumin during the synthesis process, a core-shell structure was formed to improve stability and biocompatibility.

Benefits of technology

The prepared quantum dots have high biological activity, low cost and good stability, and are suitable for antibacterial materials and in vivo imaging, showing excellent antibacterial activity and high fluorescence properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795905A_ABST
    Figure CN120795905A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of protein coupled water-phase CuInS quantum dots, and belongs to the technical field of luminescent materials. The method comprises the following steps: respectively preparing a GSH solution, an SC solution, a Cu solution, an In solution, an MPA solution, a Zn solution, an S solution, a lysozyme solution or a bovine serum albumin solution, and reacting the Cu solution, the In solution, the GSH solution, the SC solution and the S solution to obtain a CIS suspension; the preparation method comprises the following steps: firstly adding a Zn solution into a CIS suspension, then adding a Lys solution or a BSA solution, an MPA solution and an SC solution, carrying out a complexation reaction, adding an S solution after complexation is completed, and obtaining the protein-coupled water-phase CuInS quantum dots in one pot in two steps, which are respectively marked as CuInS / ZnS-coated Lys core-shell quantum dots and CuInS / ZnS-coated BSA core-shell quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a preparation method and application of protein-coupled CuInS quantum dots in an aqueous phase, and belongs to the technical field of luminescent materials. BACKGROUND

[0002] As an important semiconductor nanomaterial, quantum dots are widely used in various fields due to their excellent optical properties. However, traditional II-VI quantum dots (such as CdSe, PbS) are severely limited in biological application potential due to biological toxicity and environmental accumulation risk, which has given rise to an urgent need for low-toxicity substitutes. Therefore, ternary I-III-VI quantum dots (I=Cu + , Ag + ; III=Al 3+ , Ga 3+ , In 3+ ; VI=S 2- , Se 2- , Te 2- ) composed of non-toxic elements are developed and used for cell labeling, tumor imaging, biomarker detection and the like. However, some of its applications are still restricted by the undeveloped synthesis technology. On the one hand, it is necessary to develop a green aqueous synthesis strategy to construct ternary quantum dots with high fluorescence intensity. On the other hand, the stability of ternary quantum dots needs to be further improved to meet the application requirements in complex biological systems.

[0003] Using natural biological macromolecules such as proteins as modifiers is a classic strategy to obtain functional inorganic nanomaterials with high biocompatibility and high stability. On the one hand, the rich thiol, amino and carboxyl groups on the structure of proteins are easy to form covalent bonds with active molecules, which is convenient for functional modification. On the other hand, the intrinsic activity of proteins can also endow nanomaterials with special properties. Generally speaking, protein-modified nanomaterials can be completed by combining protein post-modification with the surface of nanomaterials or participating in the growth process of nanomaterials during the synthesis process. The post-modification strategy has a certain prospect, but it increases the workload of synthesis, and the modification process is difficult to control, which is easy to cause adverse phenomena such as aggregation of quantum dots.

[0004] In recent years, it has been reported that by adding proteins to modify cadmium-based binary quantum dots during the synthesis process, the results show that the proteins significantly enhance the stability and biocompatibility. So far, there is no report on the construction of I-III-VI ternary aqueous quantum dots by incorporating proteins in the shell. In view of the deficiencies of the prior art, the application provides a preparation method of protein-coupled CuInS / ZnS quantum dots. SUMMARY

[0005] Therefore, the application provides a preparation method of protein-coupled aqueous CuInS quantum dots.

[0006] Specifically, the application is realized by the following scheme:

[0007] A preparation method of protein-coupled aqueous CuInS quantum dots, wherein a reduced glutathione (GSH) solution, a sodium citrate (SC) solution, a copper (Cu) liquid, an indium (In) liquid, a 3-mercaptopropionic acid (MPA) solution, a zinc (Zn) liquid, a sulfur (S) liquid, a lysozyme solution or a bovine serum albumin solution are respectively configured,

[0008] Step one, the Cu liquid, the In liquid, the GSH solution, the SC solution and the S liquid are reacted to obtain a CIS suspension;

[0009] Step two, the Zn liquid is first added to the CIS suspension, and then the lysozyme (Lys) aqueous solution or the bovine serum albumin (BSA) solution and the MPA solution, the SC solution are added for complexation reaction, and the S liquid is added after the complexation is completed, so as to obtain protein-coupled aqueous CuInS quantum dots in one pot and in two steps, which are respectively denoted as CuInS / ZnS@Lys core-shell quantum dots and CuInS / ZnS@BSA core-shell quantum dots.

[0010] In the above preparation process, the first step is to synthesize CuInS (denoted as CIS) core quantum dots by reacting the copper liquid, the indium liquid, the GSH solution, the SC solution and the sulfur liquid, and the second step is to grow a ZnS shell on the CIS core quantum dots in situ and to couple and complex Lys or BSA on the surface of the core quantum dots by chemical coordination to obtain CuInS / ZnS@Lys or CuInS / ZnS@BSA core-shell quantum dots.

[0011] Further, as a preferred solution:

[0012] In step one,

[0013] The Cu liquid is an aqueous solution of CuBr2, the In liquid is an aqueous solution of InBr3, the GSH solution is an aqueous solution of GSH, the SC solution is an aqueous solution of SC, and the S liquid is an aqueous solution of thiourea.

[0014] Cu 2+ , In 3+ , GSH, SC and S are in a molar ratio of 1:4:24:8:2.

[0015] The reaction temperature is 98℃, and the reaction time is 60 min.

[0016] In step two,

[0017] Zn liquid is an aqueous solution of Zn(Ac)2·2H2O, and MPA solution is an aqueous solution of trimercapto propionic acid.

[0018] Zn 2+ The molar ratio of Zn, MPA, SC, Lys and S is 2:4:2:28-48:1.

[0019] Zn 2+ The molar ratio of Zn, MPA, SC, BSA and S is 2:4:2:0.0012-0.0042:1.

[0020] The temperature of the complexing reaction is 98 DEG C, and the reaction time is 60 min.

[0021] Secondly, the applicant also provides the application of the product prepared by the above method, and the above method prepares two products:

[0022] The product one is CuInS / ZnS@Lys core-shell quantum dots, which is used for the preparation of antibacterial materials, and experiments prove that the quantum dot material prepared by the application has good antibacterial activity on escherichia coli and staphylococcus aureus. At the same time, the reaction system is green and environmentally friendly, the production cost is low, and the stability is good. Therefore, it can be applied to the preparation of materials for resisting escherichia coli and staphylococcus aureus.

[0023] In the experiment, we also found that the above-mentioned CuInS / ZnS@Lys core-shell quantum dots can also complete in vivo imaging.

[0024] The product two is CuInS / ZnS@BSA core-shell quantum dots, which is used as a new type of water-soluble core-shell quantum dot, has the advantages of good biocompatibility, high fluorescence and low cost, and is used for biological in vivo imaging. Experiments prove that the quantum dot material prepared by the application has good fluorescence imaging effect in mice. At the same time, it has the advantages of low toxicity, environmental protection, good biocompatibility and high stability.

[0025] The application has the following beneficial effects:

[0026] 1. The synthesis method of the protein-coupled CuInS / ZnS quantum dots synthesizes a new type of ternary aqueous quantum dots by taking cuprous bromide, indium tribromide, thiourea, glutathione, sodium citrate, zinc acetate dihydrate and lysozyme solution as raw materials, and compared with pure CuInS / ZnS quantum dots, the fluorescence lifetime, fluorescence emission intensity and stability in physiological environment are improved.

[0027] 2. The CuInS / ZnS@Lys quantum dots prepared by the present invention can be applied to different medical scenarios, such as in vivo antibacterial, mouse wound treatment, and medical catheter antifouling, with a sterilization rate of up to 99.48% and 94.96% against Staphylococcus aureus and Escherichia coli.

[0028] 3. The present invention synthesizes bovine serum albumin-coupled CuInS / ZnS aqueous quantum dots, namely CuInS / ZnS@BSA core-shell quantum dots. The reaction system is green and environmentally friendly, with low preparation cost, significantly improved physiological environment stability, and its high fluorescence properties can be used for biological imaging.

[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0031] Figure 1 TEM image of CuInS / ZnS (CIS / ZnS) core-shell quantum dots prepared in Example 1;

[0032] Figure 2 Characterization results of CuInS / ZnS@Lys (CIS / ZnS@Lys) core-shell quantum dots prepared in Example 2;

[0033] a: TEM image of CIS / ZnS@Lys QDs, b: UV-visible absorption spectrum of CIS / ZnS@Lys QDs,

[0034] c: Fluorescence lifetime diagram of CIS / ZnS@Lys QDs, scale bar = 50 nm,

[0035] d: XPS full spectrum of CIS / ZnS@Lys QDs;

[0036] Figure 3 High-resolution comparison spectra of CIS / ZnS QDs and CIS / ZnS@Lys QDs.

[0037] (a) High-resolution contrast spectrum of Cu 2p, (b) High-resolution contrast spectrum of In 3d, (c) High-resolution contrast spectrum of S, (d) High-resolution contrast spectrum of Zn 2p;

[0038] Figure 4 For different Zn 2+Optical properties of CuInS / ZnS@Lys quantum dots prepared with different Lys molar ratios

[0039] a: different Zn 2+ Fluorescence spectra of CIS / ZnS@Lys prepared with different Lys molar ratios

[0040] b: different Zn 2+ Fluorescence lifetime of CIS / ZnS@Lys prepared with different Lys molar ratios

[0041] c: different Zn 2+ Photos of CIS / ZnS@Lys prepared with different Lys molar ratios under UV lamp

[0042] d: different Zn 2+ Photos of CIS / ZnS@Lys prepared with different Lys molar ratios under daylight lamp

[0043] Figure 5 Characterization results of CuInS / ZnS@BSA (CIS / ZnS@BSA) core-shell quantum dots prepared in Example 3

[0044] a: TEM image of CIS / ZnS@BSA QDs; b: XRD comparison chart of CIS / ZnS@BSA QDs

[0045] c: XPS full spectrum chart of CIS / ZnS@BSA QDs

[0046] Figure 6 High-resolution comparison chart of CIS / ZnS QDs and CIS / ZnS@BSA QDs,

[0047] (a) High-resolution comparison chart of Cu 2p, (b) High-resolution comparison chart of In 3d, (c) High-resolution comparison chart of S, (d) High-resolution comparison chart of Zn 2p

[0048] Figure 7 Different Zn 2+ Optical properties of CuInS / ZnS@BSA quantum dots prepared with different BSA molar ratios

[0049] a: UV-visible absorption spectrum chart, b: Fluorescence spectrum chart, c: Fluorescence lifetime chart

[0050] Figure 8 Agarose gel electrophoresis chart of CIS / ZnS series quantum dots

[0051] a: Agarose gel electrophoresis chart of incubation of CIS / ZnS quantum dots (i), CIS / ZnS@Lys quantum dots (ii) and CIS / ZnS+Lys (iii); b: Bright field chart

[0052] Figure 9 CIS / ZnS@Lys treated E. coli and S. aureus colony change chart prepared for application example 2.

[0053] Figure 10 Enzyme activity chart of CIS / ZnS@Lys prepared for application example 2.

[0054] Figure 11 Model chart of CIS / ZnS@Lys prepared for application example 2 in mouse wound infection treatment;

[0055] a: treatment effect on mouse wound infection caused by S. aureus; b: photograph; c: relative wound area;

[0056] Figure 12 Application chart of CIS / ZnS@Lys prepared for application example 2 in medical catheter antifouling;

[0057] a: medical catheter chart; b: catheter fluorescence chart after CIS / ZnS@Lys treatment; c: fluorescence chart of quantum dots and S. aureus co-incubation; d: catheter colony chart before CIS / ZnS@Lys quantum dot treatment; e: catheter colony chart after treatment;

[0058] Figure 13 Fluorescence imaging chart of CuInS / ZnS@Lys, CuInS / ZnS@BSA quantum dots prepared for application example 2 and application example 3 in mouse live body, i) CIS / ZnS, ii) CIS / ZnS@BSA, iii) CIS / ZnS@Lys;

[0059] Figure 14 Fluorescence stability of CIS / ZnS quantum dots,

[0060] (a) relative fluorescence intensity of CIS / ZnS QDs incubated in different physiological buffer solutions (i: H2O, ii: NaCl, iii: PBS, iv: DMEM, v: LB, vi: SERUM) for different times, (b) corresponding daylight chart photograph in (a), (c) corresponding fluorescence image in (a);

[0061] Figure 15 Fluorescence stability of CIS / ZnS@Lys quantum dots,

[0062] (a) The relative fluorescence intensity of CIS / ZnS@Lys QDs incubated in different physiological buffer solutions (i: H2O, ii: NaCl, iii: PBS, iv: DMEM, v: LB, vi: SERUM) for different time, (b) The corresponding sunburst plot of (a);

[0063] Figure 16 Cell viability plots of CIS / ZnS, CIS / ZnS@Lys, and CIS / ZnS@BSA QDs. DETAILED DESCRIPTION

[0064] In order to make the technical problems, technical solutions and beneficial effects to be solved in the present application more clear and explicit, the technical solutions in the embodiments of the present application will be further described in detail below with reference to the drawings in the embodiments of the present application. It should be understood that the specific embodiments described herein are only used to explain the present application, and are not used to limit the technical solutions of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0065] Embodiment 1

[0066] In this embodiment, water-phase CuInS / ZnS QDs were prepared.

[0067] 1. Preparation of CIS core quantum dots: accurately weigh each precursor reagent according to the stoichiometric ratio, and prepare the core precursor solution.

[0068] Copper solution: weigh CuBr2 solid 223.35 mg, dissolve in deionized water 50.0 mL;

[0069] Indium solution: weigh InBr3 solid 709 mg, dissolve in deionized water 5.0 mL;

[0070] Ligand solution one: weigh reduced glutathione (GSH) 736.8 mg, dissolve in deionized water 6.0 mL;

[0071] Ligand solution two: weigh sodium citrate dihydrate 1.84 mg, dissolve in deionized water 10.0 mL;

[0072] Sulfur solution: weigh thiourea 76 mg, dissolve in deionized water 10.0 mL.

[0073] At room temperature and normal pressure, CuBr2(0.02M, 5.0mL), InBr3(0.4M, 1.0mL), reduced glutathione (0.4M, 6.0mL) and sodium citrate dihydrate (0.4M, 2.0mL) solution were sequentially mixed into a three-necked flask, a total of 14mL, at this time, the solution became a milky white suspension. Then the pH value of the mixed solution was quickly adjusted to 10.0 with NaOH solution (1.0M), and the solution was transparent. Thiourea (0.1M, 1.0mL) was quickly injected into the mixture solution, and stirred for 5min. The reaction system was heated to 98℃ for 35min to prepare the aqueous phase CIS core QDs.

[0074] 2. Accurately weigh each precursor reagent according to the stoichiometric ratio to prepare the shell precursor solution.

[0075] Zinc solution: prepare a 0.1M Zn(Ac)2·2H2O solution, weigh 439.02mg of zinc acetate dihydrate and dissolve in 20.0mL of deionized water;

[0076] MPA solution: prepare a 0.1M solution of trimercapto propionic acid, weigh 212.2mg of trimercapto propionic acid and dissolve in 20.0mL of deionized water;

[0077] Zn liquid (0.2mmol 1mL) was injected into the CIS reaction liquid, and MPA (0.4mmol 4mL) solution and SC solution (0.2mmol 0.5mL) solution were quickly added in sequence, and after complexation, thiourea solution (0.1mmol, 1mL) was quickly injected, a total of 7.5mL, the reaction system was reacted at 98℃ for 60min to obtain CIS / ZnS QDs.

[0078] Figure 1 The TEM spectrum of the aqueous phase CIS / ZnS QDs prepared by the above method is shown in FIG. 2. As shown in FIG. 2, the prepared aqueous phase CIS / ZnS QDs are uniform in size, basically spherical, have good monodispersity and small size dispersion, and the quantum dots are distributed at 2.3nm. Figure 1

[0079] Example 2

[0080] In this example, aqueous phase CuInS / ZnS@Lys core-shell quantum dots were prepared.

[0081] 1. CIS core quantum dot preparation: accurately weigh each precursor reagent according to the stoichiometric ratio to prepare the core precursor solution.

[0082] Copper solution: weigh CuBr2 solid 223.35mg, dissolve in deionized water 50.0mL;

[0083] ​Indium solution: Take InBr3 solid 709 mg, and dissolve in deionized water 5.0 mL;

[0084] Ligand solution one: Take reduced glutathione (GSH) 736.8 mg, and dissolve in deionized water 6.0 mL;

[0085] Ligand solution two: Take sodium citrate dihydrate 1.84 mg, and dissolve in deionized water 10.0 mL;

[0086] Sulfur solution: Take thiourea 76 mg, and dissolve in deionized water 10.0 mL.

[0087] At room temperature and normal pressure, CuBr2 (0.02M, 5.0mL), InBr3 (0.4M, 1.0mL), reduced glutathione (0.4M, 6.0mL) and sodium citrate dihydrate (0.4M, 2.0mL) solutions were sequentially mixed into a three-necked flask, a total of 14 mL, at this time, the solution became a milky white suspension. Then the pH value of the mixed solution was quickly adjusted to 10.0 with NaOH solution (1.0M), and the solution was transparent. Thiourea (0.1M, 1.0mL) was quickly injected into the mixed solution, and stirred for 5 min. The reaction system was heated to 98℃ for 35 min to prepare the aqueous phase CIS core QDs.

[0088] 2. Accurately weigh each precursor reagent according to the stoichiometric ratio to prepare the shell precursor solution.

[0089] Zinc solution: Prepare a 0.1M Zn(Ac)2·2H2O solution by weighing 439.02 mg of zinc acetate dihydrate and dissolving it in 20.0 mL of deionized water;

[0090] MPA solution: Prepare a 0.1M solution of trimercapto propionic acid by weighing 212.2 mg of trimercapto propionic acid and dissolving it in 20.0 mL of deionized water;

[0091] Inject Zn solution (0.2mmol 1mL) into the CIS reaction solution, and quickly add MPA (0.4mmol 4mL) solution and SC solution (0.2mmol 0.5mL) solution in sequence, and after adding the SC solution, slowly drop 1mL of lysozyme solution into the reaction solution, and increase the stirring speed to 1100r / min. After complexation, quickly inject S solution (0.1mmol, 1mL), a total of 7.5mL, and react the reaction system at 98℃ for 60min to obtain CuInS / ZnS@Lys QDs.

[0092] Figure 2 The characterization results of the above-prepared aqueous phase CuInS / ZnS@Lys QDs are shown in the following figures, Figure 2(a) shows that CIS / ZnS@Lys QDs are spheroidal, and the diameter increases to 2.8 nm; a small amount of quantum dots exist in aggregation, and the overall dispersion is uniform. Compared with standard CIS / ZnS quantum dots, Figure 2 (b) shows that the UV-Vis absorption spectrum of CIS / ZnS@Lys QDs has an additional shoulder peak at 330 nm, which proves that there is a certain combination between the protein and the quantum dots. Figure 2 (c) shows that the PL spectrum of CIS / ZnS@Lys QDs is red-shifted, which may be attributed to the fact that the lysozyme monomer has strong electron donor properties, which changes the dielectric environment of the quantum dots. Its fluorescence lifetime is greatly improved from 100 ns to 421 ns, which may be attributed to the fact that the acceptor delays the process of the QD@Lys excited state molecule to the ground state through energy transfer, i.e., the decay process of the fluorescence emission rate is delayed. While Figure 2 (d) shows that the XPS full spectrum of the quantum dots contains Cu, In, Zn and S elements. While Figure 3 The high-resolution comparison spectrum of the individual elements of CIS / ZnS QDs and CIS / ZnS@Lys QDs in (e) also confirms the success of the synthesis process in this case.

[0093] Example 3

[0094] This example has the same settings as Example 2, except that the Zn 2+ : Lys molar ratio is shown in Table 1.

[0095] Table 1: Effect of different Zn 2+ : Lys molar ratios on the fluorescence properties of quantum dots

[0096] Molar ratio Fluorescence lifetime (ns) Zn 2+ : Lys = 48 421 Zn 2+ : Lys = 36 301 Zn 2+ : Lys = 28 334

[0097] In combination with Table 1 and Figure 4 It can be seen that: with the decrease of the Zn 2+ : Lys ratio, the fluorescence intensity of CIS / ZnS@Lys quantum dots and the content of lysozyme increase inversely, and the fluorescence lifetime is improved, therefore, by adjusting the ratio of Zn 2+ : Lys, the fluorescence performance can be adjusted.

[0098] Example 4

[0099] In this example, aqueous phase CuInS / ZnS@BSA core-shell quantum dots are prepared.

[0100] 1. CIS core quantum dot preparation: accurately weigh each precursor reagent according to the stoichiometric ratio, and prepare the core precursor solution.

[0101] Copper solution: weigh CuBr2 solid 223.35 mg, dissolve in deionized water 50.0 mL;

[0102] Indium solution: Take InBr3 solid 709 mg, dissolve in deionized water 5.0 mL;

[0103] Ligand solution one: Take reduced glutathione (GSH) 736.8 mg, dissolve in deionized water 6.0 mL;

[0104] Ligand solution two: Take sodium citrate dihydrate 1.84 mg, dissolve in deionized water 10.0 mL;

[0105] Sulfur solution: Take thiourea 76 mg, dissolve in deionized water 10.0 mL.

[0106] At room temperature and atmospheric pressure, CuBr2 (0.02 M, 5.0 mL), InBr3 (0.4 M, 1.0 mL), reduced glutathione (0.4 M, 6.0 mL) and sodium citrate dihydrate (0.4 M, 2.0 mL) solution were sequentially mixed into a three-necked flask, a total of 14 mL, at this time, the solution became a milky white suspension. Then the pH value of the mixed solution was quickly adjusted to 10.0 with NaOH solution (1.0 M), and the solution was transparent. Thiourea (0.1 M, 1.0 mL) was quickly injected into the mixed solution, and stirred for 5 min. The reaction system was heated to 98℃ for 35 min to prepare the aqueous CIS core QDs.

[0107] 2. Accurately weigh each precursor reagent according to the stoichiometric ratio to prepare the shell precursor solution.

[0108] Zinc solution: Prepare a 0.1 M Zn(Ac)2·2H2O solution, take 439.02 mg of zinc acetate dihydrate, and dissolve in 20.0 mL of deionized water;

[0109] MPA solution: Prepare a 0.1 M solution of trimercapto propionic acid, take 212.2 mg of trimercapto propionic acid, and dissolve in 20.0 mL of deionized water;

[0110] Zn solution (0.2 mmol 1 mL) was injected into the CIS reaction solution, and MPA (0.4 mmol 4 mL) solution and SC solution (0.2 mmol 0.5 mL) solution were quickly added in sequence, and at the same time, 1 mL of bovine serum albumin solution was added after the SC solution was injected, and the Zn 2 + : BSA molar ratio is Zn 2+:BSA: S = 2:0.0024) was slowly added into the reaction solution, the rotation speed was increased to 1100 r / min, and after the complexation was completed, S solution (0.1 mmol, 1 mL) was quickly injected, a total of 7.5 mL, and the reaction system was reacted at 98°C for 60 min to obtain CuInS / ZnS@BSA QDs.

[0111] Figure 5 Figures of characterization results of the above-prepared water-phase QDs, Figure 5 (a) It can be seen that the CIS / ZnS@BSA quantum dots prepared in the embodiment are monodisperse spherical nanoparticles with an average diameter of 2.38 nm. Figure 5 (b) The XRD spectrum proves that the CIS / ZnS quantum dots and the CIS / ZnS@BSA quantum dots are chalcopyrite structures, Figure 5 (c) The XPS full spectrum can show that the quantum dots contain Cu, In, Zn and S elements. And Figure 6 The high-resolution spectrum of the elements of the CIS / ZnS QDs and the CIS / ZnS@BSA QDs in (d) also proves the success of the synthesis process.

[0112] Example 5

[0113] The embodiment is the same as the setting of Example 2, and the difference is that the molar ratio of Zn 2+ :BSA is shown in Table 2.

[0114] Table 2: Influence of different molar ratios of Zn 2+ :BSA on the fluorescence properties of the quantum dots

[0115]

[0116] It can be seen from Table 2 and Figure 7 It can be seen that: with the change of the molar ratio of Zn 2+ :BSA, that is, the increase of the content of BSA. The fluorescence lifetime and the fluorescence intensity of the quantum dots are both improved (see (b), (c) in Figure 7 , which may be attributed to the fact that the surface of the CIS / ZnS quantum dots is fully covered by BSA, the surface defects are reduced, and when the molar ratio of Zn 2+ :BSA = 2:0.0024, the fluorescence lifetime reaches a maximum value of 467 ns, and the fluorescence intensity is improved by 1.5 times.

[0117] The molar ratio of Cu 2+ , In 3+ , GSH, SC, S is 1:4:24:8:2, and the molar ratio of Zn 2+ , MPA, SC, Lys, S is 2:4:2:48:1, and the molar ratio of Zn 2+The CuInS / ZnS@Lys quantum dots and CuInS / ZnS@BSA quantum dots prepared under the conditions of the molar ratio of MPA, MPA, SC, BSA, S being 2:4:2:0.0042:1 are used to illustrate the application examples.

[0118] Application Example 1: Evaluation of antibacterial performance

[0119] The CuInS / ZnS@Lys quantum dots are respectively evaluated for antibacterial performance by the following methods.

[0120] 1) Plate counting method

[0121] Negative control group: the overnight cultured test strain is gradiently diluted with LB broth medium to OD 600 = 0.25 (corresponding to 1 x 10 8 CFU / mL). The LB liquid medium is diluted to a dilution of 10 -4 , the bacterial solution is mixed to ensure the uniformity of the bacterial suspension. 2.5 μL of the diluted bacterial solution is accurately taken for plate coating. The plate is inverted in the biological safety cabinet for 10 min to promote bacterial adsorption, and is incubated in a constant temperature incubator at 37℃ overnight.

[0122] Drug group: the gradient concentration of CIS / ZnS@Lys QDs (0.4 / 0.5 / 0.6 mg / mL) is mixed with an equal volume of diluted bacterial solution (10 -4 ), and the final volume is 400 μL. After incubation for 20 min, 2.5 μL is taken for plate coating. The subsequent coating and incubation steps are the same as those of the negative control group, and 3 repeats are set for each group.

[0123]

[0124] 2) Agar diffusion method

[0125] The OD 600 = 0.8 S. aureus bacterial solution and E. coli bacterial solution are coated, and after uniform coating, CIS / ZnS@Lys QDs (0.6 mg / mL 10 μg), compound sulfamethoxazole (SXT-25 μg), ampicillin (AMP-10 μg) and ciprofloxacin (CIP-5 μg) are respectively pasted on the plate, and are incubated at 37℃ overnight. The diameter of the inhibition zone is observed and measured. The size of the inhibition zone is directly proportional to the antibacterial activity of the test substance.

[0126] The agar diffusion results are shown in Figure 8 , and the antibacterial effect is shown in Figure 9 .

[0127] (1) The antibacterial effect of CuInS / ZnS@Lys (ii) is improved compared with pure CuInS / ZnS (i) quantum dots and pure lysozyme solution (see (a) in Figure 9 Figure 9 The bactericidal rate of well-designed CuInS / ZnS@Lys on Staphylococcus aureus and Escherichia coli is as high as 99.48% and 94.96% (see (b), (c) in Figure 9

[0128] (2) The CuInS / ZnS@Lys of the present application has good antibacterial activity compared with commercially available antibiotics, among which it shows superior bactericidal activity on Staphylococcus aureus, with a diameter of the inhibition zone reaching 23 mm (see (d), (e) in Figure 9

[0129] Application Example 2: Lysozyme activity

[0130] In order to evaluate the biological activity of lysozyme, a lysozyme (LZM) detection kit was used for detection. The calculation formula is:

[0131] Lysozyme content (μg / mL) = C standard × ΔA measuring tube ÷ ΔA standard tube * D.

[0132] As shown in Figure 10 , the initial concentration of lysozyme is 108.5 ± 14.6 U / ml, and after treatment with CIS / ZnS@Lys QDs prepared in Example 2, it is reduced to 63.2 ± 8.3 U / ml, retaining 60% of the lysozyme activity.

[0133] Application Example 3: Treatment of skin infection

[0134] The present scheme provides a mouse skin wound infection model to further evaluate the practical performance of CuInS / ZnS@Lys.

[0135] As shown in Figure 11 , subcutaneous injection of Staphylococcus aureus on the back of mice leads to subcutaneous abscess, establishing an infection model, and then in vivo antibacterial infection treatment is carried out at a fixed time every day (a) in Figure 11 . CIS / ZnS@Lys QDs and PBS buffer experimental groups are set. The experimental results show that for the PBS buffer solution group, abscess and ulcer appear from the inside of the skin on the 3rd day after subcutaneous injection of Staphylococcus aureus. The ulcer area gradually expands with the increase of time, and large wounds or scabs still appear on the 7th day. In contrast, the lesions of the wounds treated by CIS@Lys QDs gradually recover, the wounds heal completely, and the scars disappear on the 9th day. The infection area of each group of wounds at different times during the treatment is recorded Figure 11 ​CIS / ZnS@Lys QDs have good therapeutic effect.

[0136] Application Example 4: Antifouling of medical catheter

[0137] The present application provides the application of CIS / ZnS@Lys QDs in the antifouling of medical catheter Figure 12 (a). Figure 12 As shown in the figure, the cleaned catheter incubated with quantum dots shows no obvious fluorescence Figure 12 (b). However, the catheter treated by bacterial growth shows strong fluorescence Figure 12 (c) after incubation with CIS / ZnS@Lys, and still has weak red fluorescence after washing with PBS buffer for 3 times. In addition, CIS / ZnS@Lys treatment can significantly inhibit bacterial growth on the catheter Figure 12 (d) and (e) control). It is proved that CIS / ZnS@Lys has biomedical application potential.

[0138] Application Example 5: Live imaging of mice

[0139] The present application provides a CIS / ZnS series of quantum dots for live imaging model of mice. The specific steps are as follows: Kunming mice are used as models, and 30 μL of CIS / ZnS series of quantum dots are injected subcutaneously, and 5 min later, fluorescence imaging is performed in a chemiluminescence system to observe the fluorescence distribution of quantum dots.

[0140] As shown in the figure, the fluorescence image clearly shows that CuInS / ZnS@Lys and CuInS / ZnS@BSA quantum dots have good fluorescence imaging effect in vivo, which can be used as clinical nanofluorescent probes. Figure 13

[0141] Application Example 6: Fluorescence stability test

[0142] The present application provides a fluorescence stability test of CIS / ZnS series of quantum dots in different physiological environments. The specific steps are as follows: different physiological buffer solutions and different types of quantum dots are added in a volume ratio of 1:1 in a multi-well quartz dish, and the mixture is placed at room temperature. Fluorescence test and fluorescence imaging are performed at 0, 1, 3, 6, 9, 12, and 24 h, respectively. The percentage of fluorescence intensity decrease is calculated as follows:

[0143]

[0144] Wherein, I0 is the initial fluorescence intensity, and I t is the fluorescence intensity after a certain time or under a certain condition.

[0145] As shown in the figure, the fluorescence image clearly shows that CuInS / ZnS@Lys and CuInS / ZnS@BSA quantum dots have good fluorescence imaging effect in vivo, which can be used as clinical nanofluorescent probes. Figure 14 ​、 Figure 15 As shown, CIS / ZnS quantum dots begin to exhibit fluorescence quenching around 1 hour, aggregation occurs around 3 hours, and after 24 hours of incubation, over 90% of the quantum dots are completely quenched. The stability of CIS / ZnS@Lys quantum dots in different buffer systems is improved, with the fluorescence intensity of the QDs remaining relatively stable over the 24-hour observation period, and the fluorescence quenching rate of the quantum dots is reduced. After 24 hours of incubation, CIS / ZnS@Lys quantum dots retain 70% of their fluorescence brightness in H2O, NaCl, SERUM medium, and LB medium. 40% of the fluorescence intensity is retained in PBS buffer and 50% in DMEM medium, demonstrating improved biocompatibility of the quantum dots.

[0146] The stability and biocompatibility of CIS / ZnS@BSA quantum dots were greatly improved. The fluorescence intensity of CIS / ZnS@BSA quantum dots fluctuated within 3 hours and tended to be stable after 3 hours. After 24 hours, more than 90% of the red fluorescence was still retained.

[0147] Application Example 7: Cytotoxicity

[0148] In this case, the CCK-8 method was used to evaluate the cytotoxicity of CIS / ZnS quantum dots to mouse breast cancer cells (4T1). Figure 16 As shown in the data, with the increase of concentration, the cell survival rate decreased. When the quantum dot concentration was controlled at 100 μg / mL or below, the cell survival rate was greater than 90%, which proved that the CIS / ZnS@Lys quantum dots and CIS / ZnS@BSA quantum dots prepared in this example had good biocompatibility.

[0149] The above-described embodiments merely represent several feasible implementation methods of the present invention. The description thereof is relatively specific and detailed, but it should not be understood as limiting the scope of the invention. The embodiments are not intended to limit the scope of protection in the claims of the present invention. For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention. Any equivalent implementation or modification that does not depart from the scope of the present invention should be included in the technology of the present invention.

Claims

1. A method for preparing protein-coupled aqueous CuInS quantum dots, characterized by: Prepare GSH solution, SC solution, Cu solution, In solution, MPA solution, Zn solution, S solution, lysozyme solution or bovine serum albumin solution respectively. Step 1: Cu solution, In solution, GSH solution, SC solution, and S solution react to obtain a CIS suspension; In step 2, Zn solution is first added to the CIS suspension, and then Lys solution or BSA solution, MPA solution, and SC solution are added for complexation reaction. After the complexation is complete, S solution is added to obtain protein-coupled aqueous phase CuInS quantum dots in one pot and two steps, which are respectively recorded as CuInS / ZnS@Lys core-shell quantum dots and CuInS / ZnS@BSA core-shell quantum dots.

2. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 1, the Cu solution is an aqueous solution of CuBr2, the In solution is an aqueous solution of InBr3, the GSH solution is an aqueous solution of GSH, the SC solution is an aqueous solution of SC, and the S solution is an aqueous solution of thiourea.

3. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 1, Cu 2+ 、In 3+ , GSH, SC, and S have a molar ratio of 1: 4: 24: 8:

2.

4. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 1, the reaction temperature is 98° C. and the reaction time is 60 min.

5. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 2, the Zn solution is an aqueous solution of Zn(Ac)2·2H2O, and the MPA solution is an aqueous solution of trimercaptopropionic acid.

6. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 2, Zn 2+ The molar ratio of MPA, SC, BSA, and S is 2:4:2:0.0012-0.0042:1, and Zn 2+ The molar ratio of MPA, SC, Lys and S is 2:4:2:28-48:

1.

7. The method for preparing protein-coupled aqueous CuInS quantum dots according to claim 1, characterized in that: In step 2, the temperature of the complexation reaction is 98° C., and the reaction time is 60 min.

8. An application of protein-coupled aqueous CuInS quantum dots prepared by the method of claim 1, characterized in that: The CuInS / ZnS@Lys core-shell quantum dots are used for the preparation of antibacterial materials.

9. The use of protein-coupled aqueous CuInS quantum dots according to claim 8, characterized in that: The CuInS / ZnS@Lys core-shell quantum dots are used for resisting Escherichia coli and Staphylococcus aureus.

10. An application of protein-coupled aqueous CuInS quantum dots prepared by the method of claim 1, characterized in that: The CuInS / ZnS@Lys core-shell quantum dots and CuInS / ZnS@BSA core-shell quantum dots are used for in vivo imaging.